2018
DOI: 10.1002/jbm.a.36414
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophin‐3 released from implant of tissue‐engineered fibroin scaffolds inhibits inflammation, enhances nerve fiber regeneration, and improves motor function in canine spinal cord injury

Abstract: Spinal cord injury (SCI) normally results in cell death, scarring, cavitation, inhibitory molecules release, etc., which are regarded as a huge obstacle to reconnect the injured neuronal circuits because of the lack of effective stimulus. In this study, a functional gelatin sponge scaffold was used to inhibit local inflammation, enhance nerve fiber regeneration, and improve neural conduction in the canine. This scaffold had good porosity and modified with neurotrophin‐3 (NT‐3)/fibroin complex, which showed sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 56 publications
0
26
0
1
Order By: Relevance
“…This implies that their observed therapeutic effect is not due to cell replacement but is likely of paracrine nature as suggested by increased gene expression of neural growth factor and Nt3 in host tissue and in case of NGF in SPC-01 cells as well [23]. It has been shown that NT-3 reduces inflammation while enhancing regeneration in the injured spinal cords leading to functional improvements [35]. Our findings provided additional evidence to elucidate the mechanisms of neural progenitor cell therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that their observed therapeutic effect is not due to cell replacement but is likely of paracrine nature as suggested by increased gene expression of neural growth factor and Nt3 in host tissue and in case of NGF in SPC-01 cells as well [23]. It has been shown that NT-3 reduces inflammation while enhancing regeneration in the injured spinal cords leading to functional improvements [35]. Our findings provided additional evidence to elucidate the mechanisms of neural progenitor cell therapy.…”
Section: Discussionmentioning
confidence: 99%
“…To construct bioscaffolds with sustained NT-3 release and with a low swelling property that would allow subsequent cell seeding, we adopted a method previously used to produce NF-GS scaffolds [ 6 , 17 ]. Immunoelectron microscope (IEM) was employed to visualize the actual loading and distribution of NT-3 molecules inside the scaffolds with the aid of nanogold-conjugated secondary antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…Over recent years, accumulating evidence in both canines [ 17 ] and nonhuman primates [ 4 ] has indicated that a single neural trophic factor, NT-3, can be a potent inducer of a pro-regenerative microenvironment that favors endogenous repair after severe SCI. However, several technical hurdles must be overcome before NT-3-producing neuronal grafts with augmented efficacy in treating SCI can be generated.…”
Section: Discussionmentioning
confidence: 99%
“…NT-3 is also a very important member of the neurotrophin family, playing a crucial role in exerting neuroprotective and neuroregenerative effects that can also guide stem cell migration, as well as mediate stem cell survival and neuronal differentiation. 26 NT-3, when delivered through various vectors, has been shown to improve stem cell survival, axonal regeneration and hind-limb functional recovery in animal models of SCI. 27,28 In the present study, we found that Adv-HIF-1α treatment significantly enhanced the expression of NT-3, which may promote the migration and survival of the BMSCs and improve the functional recovery.…”
Section: Discussionmentioning
confidence: 99%
“…NT‐3 is also a very important member of the neurotrophin family, playing a crucial role in exerting neuroprotective and neuroregenerative effects that can also guide stem cell migration, as well as mediate stem cell survival and neuronal differentiation . NT‐3, when delivered through various vectors, has been shown to improve stem cell survival, axonal regeneration and hind‐limb functional recovery in animal models of SCI .…”
Section: Discussionmentioning
confidence: 99%